Trends and Determinants of Hospitalizations Among Diabetic Patients in Chile: A 4-Year Analysis (2019–2022) - De Moraes-Ferrari, G (Springer, 2025)
Background: Type 2 diabetes (T2D) is a growing public health concern in Chile, contributing significantly to hospitalizations due to acute and chronic complications. Objective: This study aims to analyze trends in T2D hospitalizations over 4 years (2019–2022), focusing on patient demographics, reasons for admission, and hospitalization outcomes. Methods: This retrospective observational study used data from the FONASA Open Data platform, covering 31,692 hospitalizations from 65 hospitals funded through the Diagnosis-Related Groups (DRG) payment mechanism. Data were analyzed for trends in age, sex, length of stay, and primary causes of hospitalization. Statistical methods included Prais-Winsten regression to assess trends and compare hospitalization rates by gender and age groups. Results: Hospitalizations increased from 4066 in 2019 to 9628 in 2022, with the mean age rising from 65.2 ± 10.6 years to 68.4 ± 11.3 years. Peripheral circulatory complications were the leading cause of hospitalization, accounting for 70.2% of cases, followed by ketoacidosis (12.2%) and ophthalmic complications (9.1%). Male hospitalizations grew significantly, from 8.6% in 2019 to 20.2% in 2022, outpacing the increase in female hospitalizations, which reached 10.2% in 2022. The mean length of stay showed variability, with a slight increase in 2022 (11.3 ± 15.8 days). Conclusions: This study highlights the increasing burden of T2D hospitalizations in Chile, particularly among older adults and male patients. Peripheral circulatory complications remain the primary cause of admission, underscoring the need for targeted interventions to improve diabetes management and reduce hospitalizations. Keywords such as diabetes mellitus, hospitalizations, complications, trends, and Chile are central to this analysis. © The Author(s) 2025.
Keywords: Type 2 diabetes; Hospitalizations; Complications; Trends; Peripheral circulatory complications; Ketoacidosis; Ophthalmic complications; Chile; Length of stay; Gender disparities; Epidemiology; Public health; Age distribution; Diabetes management; Healthcare burden